Pengaruh Program Pemutihan Pajak dan Samsat Corner terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor Samsat Kota Bengkulu - Leni Marlina; Iwin Arnova; Pedi Riswandi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine the effect of the tax amnesty program and SAMSAT corner on taxpayer compliance in paying motor vehicle tax. This study uses a quantitative research type using primary data obtained from a questionnaire of motor vehicle taxpayers. The population in this study were taxpayers who paid motor vehicle tax and participated in the tax amnesty program at SAMSAT Corner and were recorded at the Bengkulu City Samsat office in 2024. The dependent variables in this study were service quality and tax amnesty. The population in this study was 35,490 taxpayers and was determined using the Slovin formula, namely 100 respondents. The results of this study indicate that the tax amnesty program has a significant effect on taxpayer compliance and the Samsat corner has a significant effect on taxpayer compliance. The results of this study also indicate that tax amnesty and Samsat corner have a simultaneous effect on taxpayer compliance.